Resistance of Rhyzopertha dominica (Coleoptera: Bostrichidae) to phosphine fumigation; geographic variation, high dose treatments and rapid assay assessment - Afful, Edwin (Kansas State University, 2018)
The emergence of heritable high-level resistance to the fumigant gas phosphine in stored-product insects is of grave concern to many grain growing countries around the world. The research reported in this dissertation was designed to determine the presence of phosphine resistance in 34 field collected populations of Rhyzopertha dominica (F.) from the United States and Canada, the potential to control resistant R. dominica populations utilizing high dose and longer exposure time strategies, and to develop a rapid assay for phosphine resistance detection. Using a discriminatory dose assay called the FAO number 16 method, adult R. dominica were sampled and subjected to a phosphine dose of 20 ppm for a fumigation exposure period of 20 h to distinguish a susceptible R. dominica adult by death from a resistant beetle that survives the treatment. Results from the study showed that 32 out of the 34 geographic populations surveyed had beetles resistant to phosphine, and the frequency of resistance varied from 97% in a population from Parlier, California to 0% in beetles from both Carnduff, Saskatchewan and Starbuck, Manitoba. A 20-hour dose response assay was used to characterize the level of resistance by calculating the resistance ratio factors using beetles from a laboratory susceptible strain and those from five of the populations sampled. This resistance ratio (RR) was based on the ratio of LC50 (estimate for the concentration to kill 50% of a test group) in the sampled population to the LC50 for the susceptible strain. The highest RR for the five resistant populations was nearly 596-fold in beetles from Belle Glade, Florida, which represented the “strong” resistance phenotype, whereas the lowest RR in that group was 9-fold in Wamego, Kansas, representing the “weak” resistance phenotype. Manipulation of concentration and exposure periods can be utilized to manage strongly resistant R. dominica populations. The effect of several phosphine concentrations and fumigation exposure periods were assessed on progeny of mixed life stage colonies of the strongly resistant R. dominica. A 48 hours dose response assay was carried out on these two strongly resistant populations to re-characterize their levels of resistance. Results from this assay showed that a phosphine dose of 730-870 ppm could control all resistant adult R. dominica. Additionally, phosphine concentrations ranging from 400-800 ppm phosphine for 96 hours completely killed mixed life stage colonies of strongly resistant lesser grain borers from the two populations studied. Lastly, fumigations done beyond 4 days at phosphine concentrations between 450-700 ppm controlled all phosphine resistant populations of lesser grain identified from our previous work. Phosphine applied at high concentrations is known to elicit a knockdown effect that can vary between susceptible and resistance grain insects. Using 18 of the 34 R. dominica populations this study sought to determine among three knockdown time (KT) techniques which method had potential to be utilized in an effective rapid assay for phosphine resistance in R. dominica. Adult R. dominica were exposed to a high concentration of phosphine (3000 ppm) to assess the time to knockdown 50%, 100% of a group of ten insects and that of single insects from the 18 geographically distinct populations vis a vis the resistance frequencies using the FAO method. KT100 quick test was better than the KT50 and Ktsingle, because bioassays were able to clearly distinguish among susceptible, weak and strong resistant individuals. Time for KT100 from susceptible populations did not exceed 30 minutes, while resistant populations had KT100 times above 30 min, with strong-resistant populations times longer than 100 min.
Keywords: resistance; Rapid assay; Fumigation; Stored grain; Lesser Grain BorerPhosphine